2006
DOI: 10.1242/dev.02386
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling restricts hemato-vascular development from lateral mesoderm during somitogenesis

Abstract: The bone morphogenetic protein (BMP) signaling pathway is essential during gastrulation for the generation of ventral mesoderm, which makes it a challenge to define functions for this pathway at later stages of development. We have established an approach to disrupt BMP signaling specifically in lateral mesoderm during somitogenesis, by targeting a dominant-negative BMP receptor to Lmo2+ cells in developing zebrafish embryos. This results in expansion of hematopoietic and endothelial cells, while restricting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…Furthermore, when BMP signaling was disrupted in lateral mesoderm in the zebrafish model, by targeting a dominant-negative BMP receptor to Lmo2 þ cells, it was concluded that BMP signaling continues to function in the regulation of lineage specification after lateral mesoderm commitment. 57 However, at this stage, BMP signaling functions to restrict hemato-vascular fate in favor of pro-nephric development, 57 indicating that the effect of BMP signaling on hematopoiesis is affected by the exact stage of development. Moreover, in both murine and human embryonic stem cells, exposure to BMP4 has been reported to induce mesoderm formation, including hematopoietic commitment.…”
Section: Bmp Signaling In Hematopoietic Developmentmentioning
confidence: 99%
“…Furthermore, when BMP signaling was disrupted in lateral mesoderm in the zebrafish model, by targeting a dominant-negative BMP receptor to Lmo2 þ cells, it was concluded that BMP signaling continues to function in the regulation of lineage specification after lateral mesoderm commitment. 57 However, at this stage, BMP signaling functions to restrict hemato-vascular fate in favor of pro-nephric development, 57 indicating that the effect of BMP signaling on hematopoiesis is affected by the exact stage of development. Moreover, in both murine and human embryonic stem cells, exposure to BMP4 has been reported to induce mesoderm formation, including hematopoietic commitment.…”
Section: Bmp Signaling In Hematopoietic Developmentmentioning
confidence: 99%
“…The control of Bmp dose is vital for normal development of the various mesodermal compartments and also for normal hematopoiesis (27). However, although Smads in general play an essential role in hematopoiesis (reviewed in ref.…”
Section: Bmp4mentioning
confidence: 99%
“…However, recent gain-or lossof-function manipulation of the BMP signal pathway during middle or late gastrulation or even post-gastrulation suggested that BMP signaling also functions in blood fate specification (19,21,(41)(42)(43)(44)(45). Overall, our genetic data suggest that scube1 may regulate the BMP signaling for its later role during somitogenesis in the specification of blood progenitors.…”
Section: Discussionmentioning
confidence: 60%